New records of the flower fly Lejops barbiellinii (Ceresa, 1934) (Diptera, Syrphidae) in the Atlantic Forest: integrating collection and citizen science data - Cordeiro, Danilo P.; Zocca, Cássio; Ghilardi-Lopes, Natalia P. (Entomological Communications, 2024)
Citizen science provides valuable data on species diversity worldwide. In this note, we discuss how a scientist’s opportunistic observations of biodiversity, recorded on a citizen science platform, have enriched our understanding of the geographic distribution of Lejops barbiellinii (Ceresa, 1934) (Diptera, Syrphidae), a flower fly native to Brazil’s Atlantic Forest. We also compared the number and specificity of iNaturalist records for the five most species rich families of flies in Brazil, demonstrating the potential of this platform for data acquisition of species with external morphological diagnostic characters, as for many flower fly species. This type of contribution from voluntary citizens contributes to increasing the knowledge about geographical distribution and our collective knowledge about L. barbiellinii and other flies in the Atlantic Forest.